Legitimasi Penggunan “Debt Collector” Di Perusahaan Pembiayaan Syariah Dalam Proses Eksekusi Jaminan - Perdana Nur Ambar Setyawan (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
The development of the world of sharia economy has made significant progress in this XX century. Even in Indonesia, it is started the emergence of Islamic banks and followed by other financial business sectors such as sharia insurance, syariah capital markets, and sharia leasing. Shariah financing (Leasing) became the public choice in the procurement of goods, especially vehicles because the process is fast, simple, and easy. Similar to other financing businesses that culminate in the provision of credit, the sharia leasing system also starts from the signing of contracts, binding fiduciary guarantee, and delivery of vehicles to customers. The distinction of Sharia financing is in the contracts and Islamic Economic principles that clinged in tits business process. Trust is the primary basis of the financing business, both customer and leasing company is expecting the installment be settled on time without any payment arrears. However, sometimes there are some customers who have failed payment of vehicle installment. In this situation the company will take measures to rescue the financing, executing Fiduciary guarantee. The execution process starts from delivery of warning letters to customers till taking back the collateral by its debt collector in order to smooth the process of guarantee sales. Sometimes the collateral-taking becomes a little harsh because the customers are reluctant to hand over process, whereas the legitimacy of the debt collector's action is essentially based on both Islamic Law and Positive Law in Indonesia.